Measurement of waist circumference at four sites and its relationship with obesity indicators in children of 6 to 11 years - Flores-Olivares, Luis Alberto (Universidad Autónoma de Tamaulipas, 2019)
Waist circumference (WC) is used in the assessment of childhood obesity, however different measurement areas are used, and the similarity or difference between the values of each area has not yet been demonstrated. The aim of this research was to identify the WC area that can best determine childhood obesity, contrasting it with indicators of obesity in children. WC was measured in four different areas: 1) Minimum (MC), Umbilical (UC), midpoint (MPC) and just above the iliac crest (ICC). Endomorphy (Endo), average sum of six skinfolds (PSSS) and body mass index (BMI) were me- asured as over-weight and obesity indicators in 107 children from 6 to 11 years old. ICC was higher than MC and MPC in girls (P = 0.001 y 0.049 respectively); also UC was higher than MC (P = 0.025) in this group. All measurement areas correlated well with obesity indicators (P = 0.001). The ICC was better best measurement area to predict adiposity represented by Endo, PSSS and IMC in school age girls and boys (P = 0.001) and seems to evidence the sexual dimorphism in girls. Therefore, measurement areas must not be taken interchan- geably since this identification would help to generate a better diagnosis of obesity and metabolic risk in boys and girls during puberty.